INTERNATIONALIZATION OF HIGHER EDUCATION: ESSENCE, CONCEPTS AND COMPONENTS - Маланюк, Назарій; Zapukhliak, Ivanna Bogdanivna (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
The article deals with the concepts of internationalization and internationalization of higher education. The modern challenges and problems in higher education that have reduced the value of higher education and its necessity are considered. The necessity of forming an “open” education - education that has no boundaries and borders; education that is able to develop the ability to work in a multicultural environment, etc. is substantiated. The approaches of scholars to the concept of internationalization of higher education are studied, on the basis of which it is established that, in general, the internationalization of higher education can be considered as a process of including international, intercultural and global dimensions in the purpose, functions and provision of higher education. It is proved that higher education is still the best way to transform society and its individuals; a platform for combining individual intellects, their joint development and accumulation; a bridge for combining different cultures, skills and abilities. The approaches to the concept of internationalization of higher education are distinguished, in particular: the activity approach, which promotes such activities as international study programs, student/teacher exchange, technical assistance and training of foreign students; the competence approach emphasizes the development of skills, knowledge, attitudes and values of students, teachers and staff; the value approach, which is focused on creating a culture or climate in the organization that values and supports the intercultural, international development of the institution; the process approach, which provides for the It is established that internationalization is a complex and comprehensive process that involves the implementation of a number of individual components. At the same time, internationalization practices contain somewhat different elements, but they have in common international training, scientific cooperation and joint research, and the formation of a multicultural participant in the educational process, both students and teachers. At the same time, student mobility and teacher mobility are dominant today. It is proved that the internationalization of educational institutions opens not only new opportunities for their development, but is an objective condition for their functioning in the context of globalization of the educational and scientific space, gaining competitiveness in the national markets of educational services.